The role of ultrasound imaging at detecting aortic aneurysm in emergency department - Eraybar, Suna; Akköse Aydın, Şule; Özkan, Meral Leman; Atmaca, Serhat; Nennicioglu, Yasemin (The European Research Journal, 2019)
Objective: Our study was carried out to investigate the effects of focused ultrasound imaging which is performed by emergency physicians in diagnosis and duration of treatment of abdominal aortic aneurysm.Methods: The patients over 50 years; who applied to Uludağ University Emergency Department with the complaints of abdominal pain, side pain, chest pain, syncope, unexplained hypotension and under suspicion of the abdominal aortic aneurysm, were included in the study. Bedside ultrasound for abdominal aorta was done and diameter measurements of aorta recorded in order to determine the presence of an abdominal aortic aneurysm or to exclude the diagnosis.Results: A total of 133 patients were included in the study. Eight patients were excluded from the study because of inadequate bedside US imaging. The aortic diameter was measured as ≥ 3 cm in the 54 (43.2%) patients. The aortic diameter was found more than 5 cm  in 8 (6.4%) patients. After ultrasonographic investigations, aneurysm rupture (n = 5; 4%), aortic dissction (n = 13; 10.4%) and aortic aneurysm (n = 36; 28.8%) were detected. The diagnosis was confirmed with computed tomography in all patients who had aortic pathology. Because of the continuance of clinic suspects in the patients whose aortic diameters were less than 3 cm, their computed tomography images were obtained and their aortic diameters were found within normal limits. Further imaging studies weren’t performed at the remaining 48 (38.4%) patients because different prediagnosis was considered. Emergency ultrasound had a sensitivity of 100% (95% CI: 87-100), a specificity of 91% (95% CI: 90.8-99.8). Conclusions: The diagnosis of abdominal aortic aneurysms is omitted 30% in emergency departments. It has a high morbidity and mortality if the diagnosis is skipped. In the presence of aortic aneurysm suspicion, evaluation of aortic diameter by bedside ultrasound is diagnostic. Bedside ultrasound evaluation by emergency physicians should become routine for using time and investigation numbers properly.